2007
DOI: 10.2174/138955707781662663
|View full text |Cite
|
Sign up to set email alerts
|

5-HT7 Receptor Ligands: Recent Developments and Potential Therapeutic Applications

Abstract: The 5-HT(7) receptors (5-HT(7)Rs) are the most recent classified members of the serotonin family. Characterized in 1993, they belong to the G protein-coupled receptor family. Since their discovery, they have been the subject of intense research due to their widespread distribution in the brain, suggestive of multiple central roles. The focus of this review is to discuss the literature concerning recent advances on 5-HT(7)Rs and their ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 75 publications
0
28
0
1
Order By: Relevance
“…Many ligands have been reported to bind with high affinity to 5-HT 7 receptors and their number is continuously increasing. [17][18][19] In the course of a program aimed at the discovery of new serotonine 5-HT 7 ligands, we submitted to binding assays a range of N-substituted (5-methoxy-3,4-dihydro-2H-1-benzopyran-3-yl)amine derivatives previously studied as 5-HT 1A receptor ligands. [20][21][22] We found that two of them (5-MeO-DPAC and S 20244) displayed significant affinity for 5-HT 7 R. Subsequently, we planned This lack of selectivity has led us to translate the knowledge acquired in the benzopyran series, to aminopyrrolothienopyrazine series, which has been described recently as being the possible support of new 5-HT ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Many ligands have been reported to bind with high affinity to 5-HT 7 receptors and their number is continuously increasing. [17][18][19] In the course of a program aimed at the discovery of new serotonine 5-HT 7 ligands, we submitted to binding assays a range of N-substituted (5-methoxy-3,4-dihydro-2H-1-benzopyran-3-yl)amine derivatives previously studied as 5-HT 1A receptor ligands. [20][21][22] We found that two of them (5-MeO-DPAC and S 20244) displayed significant affinity for 5-HT 7 R. Subsequently, we planned This lack of selectivity has led us to translate the knowledge acquired in the benzopyran series, to aminopyrrolothienopyrazine series, which has been described recently as being the possible support of new 5-HT ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric disorders related to depression, anxiety, and mood, learning and memory, epilepsy, inflammatory processes, and ileum peristalsis are only a few examples among all known implications of the 5-HT 7 receptors [4][5][6][7][8] . Even though the number of ligands cited in the literature is considerable 6 , 9-11 and mostly of antagonist character (1 12 and 2 13 , Figure 1), the 5-HT 7 R functions are still hindered because of the small number of highly selective ligands of agonist type, compound 3 14 belonging to the few examples reported to date (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Medicinal chemistry research had successfully obtained highaffinity and selective ligands for each of these receptors with the aim to clarify their role in the above mentioned physiological and pathological processes. [3][4][5] Recently, part of the research efforts have been directed towards the development of ligands for both receptors. Particularly, a number of studies suggest that ligands with partial agonist at 5-HT 1A R and antagonist properties on 5-HT 7 R can display antidepressant-like effects.…”
mentioning
confidence: 99%
“…of pharmacological tools [3][4][5] and successfully developed drugs, such as buspirone, gepirone, tandospirone, and aripiprazole. 6,10 The drug potential of LCAPs had led to various SAR studies focused on the three main structural features of these agents ( Fig.…”
mentioning
confidence: 99%